2008
DOI: 10.3892/or.19.4.1021
|View full text |Cite
|
Sign up to set email alerts
|

Platelet production and related pathophysiology in acute myelogenous leukemia at first diagnosis: Prognostic implications

Abstract: Among various laboratory and clinical features megakaryocytopoiesis and platelet (PLT) counts have been previously insufficiently evaluated for their prognostic significance in acute myelogenous leukaemia (AML). We studied several clinical and laboratory features of 108 first diagnosed AML patients in relation with their prognosis. Patients with favourable prognostic features were excluded from the study. This study focused on the prognostic impact of PLT counts and related molecular biology in AML patients at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…We further noted that these effects were more profound in intermediate-risk patients than favorable and adverse-risk AML patients. These findings were consistent with other investigations that lower PLT count predicted better survival in intermediate-risk group [ 24 , 32 ]. Moreover, hyperleukocytosis defined as WBC > 100 × 10 9 /L at diagnosis was demonstrated to relate with increasing early mortality in AML patients [ 10 , 33 ], which prognostic significance in RFS is not widely recognized [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We further noted that these effects were more profound in intermediate-risk patients than favorable and adverse-risk AML patients. These findings were consistent with other investigations that lower PLT count predicted better survival in intermediate-risk group [ 24 , 32 ]. Moreover, hyperleukocytosis defined as WBC > 100 × 10 9 /L at diagnosis was demonstrated to relate with increasing early mortality in AML patients [ 10 , 33 ], which prognostic significance in RFS is not widely recognized [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…Some research showed that AML patients with medium PLT count at diagnosis in the range of 50–120 × 10 9 /L had longer OS and DFS than the other patients [ 24 ]. Others reported that pretreatment PLT count > 130 × 10 9 /L was an unfavorable prognostic factor for chemotherapy response and prognosis in AML patients [ 32 ]. Although cut-off value of PLT count was various in different studies, these clinical data demonstrated that higher PLT count harbored a negative impact on survival of AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…Dimitrios indicated that group 3 (pretreatment PLT counts of > 130 × 10 9 /L) had the worst prognosis compared with group 1 (pretreatment PLT count of < 25 × 10 9 /L) and group 2 (pretreatment PLT counts 25–130 × 10 9 /L); group 3 had favorable prognostic features, high levels of endogenous thrombopoietin (TPO), and high expression of TPO receptor (C-MPL), but with low chemotherapy response and poor prognosis [ 18 ]. The TPO/MPL regulatory pathway plays a critical role in the interaction of human leukemic stem cells (LSCs) with the hematopoietic microenvironment; the upregulation of the TPO/c-MPL signaling pathway may protect the LSCs from the effects of chemotherapy as treatment for AML and is associated with chemoresistance and AML recurrence [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several studies have shown a negative correlation between platelet count and OS before treatment, which can be used as an independent predictor of AML prognosis [25][26][27][28][29][30] . Other factors related to initial platelets, including rebound thrombocytosis, platelet production, and platelet recovery time after platelet induction chemotherapy, are independent prognostic predictors of AML or acute lymphocytic leukemia (ALL) Index [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%